Binatang-Binatang di Sekitar Letusan Krakatau 1883 - Gustaman, Budi (Jurnal Sejarah, 2019)
Abstracts This study attempts to question the existence of animals in around Kratatau’s Eruption 1883. Narratives about animals actually often appear in post-disaster reports. In a disaster, animal behaviour is usually mentioned as marker of disaster. Although the truth is still questionable until now. In the disaster of 1883, Simon Winchester (2006) explained about some strange of animal behaviour before the eruption. This was also noted by several witnesses such as Rogier Verbeek and R.A. van Sandick. In addition, some reports mentioned the waves killed many livestock, fields, and plants. The continued impact of Krakatau’s eruption caused deforestation, population movements and changes of the agricultural system in South-Banten. Finally, a few years after eruption the tiger plague attacked many people in the region.